Given - Taylor, Nandi (Wattpad Books, 2021)
Yenni, a fierce Yirba warrior princess, finds herself alone in the magical empire of Cresh, desperately seeking a cure for her father's wasting illness, when she encounters the compelling and powerful dragon known as Weysh.